Sarcoidosis in the UK: insights from British Thoracic Society registry data. Issue 1 (18th February 2019) - Thillai, Muhunthan; Chang, William; Chaudhuri, Nazia; Forrest, Ian; Ho, Ling-Pei; Lines, Sarah; Maher, Toby M; Spencer, Lisa G; Spiteri, Monica; Coker, Robina
Abstract : Introduction: The British Thoracic Society Sarcoidosis Registry allows physicians to record clinical data after gaining written consent from patients. The registry's aim is to phenotype sarcoidosis in the UK. Methods: Between February 2013 and July 2017, demographic details for 308 patients (with complete clinical data for 205 patients) presenting to 24 UK hospitals were recorded. This data was analysed to detail methods of presentation, diagnosis and management. Results: Fatigue was a significant complaint, affecting 30% of all patients. The most prevalent CT findings were nodules (in 77% of cases) with traction bronchiectasis (11%), distortion (9%) and ground glass (5%) less prominent. Of 205 patients with complete clinical data, only 64% had a diagnostic tissue biopsy. 35% of all patients underwent endobronchial ultrasound-guided transbronchial needle aspirate (EBUS-TBNA) with 15% having a transbronchial biopsy. Use of EBUS-TBNA showed an overall increase over time, from 28% of all patients in 2013 to 43% in 2016. The most common steroid sparing treatment was methotrexate, but 42% of patients were not initiated on any pharmacological treatment at the time of inclusion. Discussion: Fatigue was common and has shown association with poor quality of life. We therefore suggest using a fatigue questionnaire as part of all new patient assessments. It may be that EBUS-TBNA should be reserved for cases of stage I or II disease where there is a reported higher yield than using transbronchial biopsy alone. Bronchoalveolar lavage was not widely used in our data, but it is generally a safe and useful adjunct and should be used more widely.